KONSEP DIRI REMAJA MUSLIM PENGGUNA BAHASA JAWA KRAMA - Witri Nur Laila (Profetik: Jurnal Komunikasi, 2016)
This research aims to describe the Moslem teenagers’ self-concept so that they use Krama Javanese Language consistently. Islam has rule on Moslem personality building and its also applying in Javanese community. The using of Krama Javanese Language in teenagers can present their Moslem Javanese personality in doing religion value and respecting culture. It is also become a part of their self-concept. The self-concept is about what they think and feel about themselves. This research is descriptive analysis. The subject of this research is Moslem teenagers about 16-20 years old in Vocational School who use Krama Javanese Language. The study found out that there is consistency level in using Krama Javanese Language on Moslem teenagers. Those are “sampurno” and “gojag-gajeg” type. “Sampurno” is used to communicate Krama Javanese Language to everyone, even though “gojag-gajeg” only to older people. The consistency occurs because of their strong personality. A strong personality is formed by positive self-concept. Keywords: Moslem teenagers, Self-concept, Krama Javanese Language